UPAYA MENINGKATKAN PRESTASI BELAJAR MATERI PENGURANGAN MELALUI MODEL CTL PESERTA DIDIK KELAS 1 SD NEGERI BUMIJO YOGYAKARTA - Saskia, Nina Ari Mega; Susanto, Bahtiar Heru (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2025)
This study aims to improve students’ academic achievement in Mathematics, specifically on subtraction material, through the implementation of the Contextual Teaching and Learning (CTL) instructional model in Grade I of SD Negeri Bumijo Yogyakarta. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The instruments used in this study included observation sheets, field notes, and learning outcome evaluation tests. The subjects of this study were 28 first-grade students at SD Negeri Bumijo. The results of the study showed an increase in students’ learning achievement from the initial conditions to cycle II. The average value of students increased from 60.64 (pre-action), to 68.93 in cycle I, and reached 83.21 in cycle II. The percentage of learning completion also increased, from 35.71% in the initial conditions, to 42.86% in cycle I, and reached 82.14% in cycle II. Based on the success criteria that have been set by the researcher, namely at least 80% of students achieve completeness, then the action is declared successful and the research is stopped in cycle II. Thus, it can be concluded that the CTL model is effective for improving student learning achievement in subtraction material.